Pelatihan dan Pendampingan Inventarisasi Aset Sekolah Sebagai Keberlanjutan Lembaga Pendidikan di SD Muhammadiyah 8 Malang - Affan, Muhammad Wildan; Irawan, Dwi; Puja, Puteri Amelia; Rayis, Dzulhijah Alkayyis; Rani, Andini Esa Dewi; Fauziah, Shinta Nur (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2025)
A key component to ensuring the long-term sustainability of educational institutions is efficient asset management. The recording and administration of school assets at Muhammadiyah Elementary School 8 "K.H. Mas Mansur" in Malang City remain difficult and unorganized, which can hinder the optimal use of these assets in the educational process. Through training initiatives and support for school asset inventory, this study aims to enhance asset management capabilities. Participatory techniques such as discussions, problem-solving, and case resolution are utilized. The expected outcomes of this program include the establishment of a well-documented asset inventory system, improved knowledge and skills among staff and teachers in asset management, and increased accountability and transparency in managing school property. It is hoped that by adopting a more methodical approach to asset management, the school will improve resource efficiency and promote the sustainability of education.